Pengembangan modul ajar materi kegiatan ekonomi berbasis education for sustainable development (ESD) - Rizka Devya Safitri; Pupun Nuryani; Mela Darmayanti (SAP (Susunan Artikel Pendidikan), 2025)
This research was conducted due to the urgent need to integrate sustainable development principles into economic activity materials to raise students' awareness of social and environmental impacts. However, learning this material is still suboptimal due to the lack of learning resources that comprehensively discuss this material.  The purpose of this research is to design teaching modules for economic activity materials based on Education for Sustainable Development (ESD). This study employs the Design and Development (D&D) method, referencing the ADDIE model. Research data was obtained through expert validation and testing. Data analysis techniques utilize both qualitative and quantitative analysis. The research outcomes consist of a teaching module comprising three chapters, designed to develop students' cognitive, socio-emotional, and behavioral domains. The learning activities in the module are structured using ESD-based methods and pedagogy relevant to the economic activity material. Based on expert validation results, the teaching module received an average rating of “Very Suitable” for use. Meanwhile, the effectiveness test using the N-Gain formula indicated that the teaching module falls into the “ Medium” category. Thus, the ESD-based teaching module has proven effective in supporting the learning process of economic activity materials.